Regent of Pahang officiates Jom Masuk IPT Zone 2 Pahang - UMP, PNC (2020)
His Royal Highness the Regent of Pahang Tengku Mahkota Tengku Hassanal Ibrahim Alam Shah Ibni Sultan Abdullah Al-Mustafa Ri’ayatuddin Billah Shah recently graced and officiated the Jom Masuk IPT Zone 2 Pahang organised by the Department of Higher Education (JPT), Ministry of Education Malaysia that saw Universiti Malaysia Pahang (UMP) as the host at the Sports Complex, UMP Gambang on 22 February 2020.